Guys and gals going for gold: The role of women`s empowerment in Olympic success - Lowen, A.; Deaner, R. O.; Schmitt, E. (Journal of Sports Economics, 2016)
We test the hypothesis that women`s empowerment correlates with women`s international athletic success. Greater gender equality (measured using the Gender Inequality Index) is associated with higher participation and medal counts in the Summer Olympic Games from 1996 through 2012. This relationship persists even after controlling for previously identified nation-level predictors of Olympic success and across alternative measures of success (such as shares of the total, percentage within each country, and medals per athlete). These results provide direct evidence for the long-standing claim that girls` and women`s international athletic achievement is linked to women`s empowerment.